FUNCIONAMIENTO FAMILIAR Y RENDIMIENTO ACADÉMICO EN ESTUDIANTES DE BACHILLERATO DE LA UNIDAD EDUCATIVA JESÚS MARTÍNEZ DE EZQUERECOCHA - AUCANCELA TOAPANTA AHILING BERENICE (2024)
The present study aims to examine how family interactions influence the academic performance of high school students at the Jesús Martinez de Ezquerecocha Educational Unit. Family functionality refers to the interaction of affective bonds among family members, involving the ability of family members to communicate effectively, resolve conflicts constructively, provide emotional support, demonstrate cohesion, and flexibility in their family roles; while academic performance is the pedagogical technical process that evaluates achievement according to intended learning objectives, grading becomes a quantitative measure of a student's performance in a specific course or subject expressed as a result of learning based on various objectives. The research was conducted with a population of 100 students, of which 80 were selected through probabilistic sampling, a mixed approach was used, with a non-experimental research design and a descriptive methodology. Data were collected through the standardized questionnaire called the Family Functioning Questionnaire (FF-SIL). Statistical analyses revealed that most students come from moderately functional families, with average grades ranging between 8 and 10. It suggests that a lower degree of family functionality could be associated with lower academic performance. These findings emphasize the importance of considering the family environment as a crucial factor in educational success. Family dynamics can significantly affect students' ability to focus on their studies and reach their maximum academic potential.